Environmental Control For Catfish Drying House Using Raspberry PI Microcontroller - Ibrahim, Mohamad Hanif (Universiti Sains Malaysia, 2018)
Catfish drying process is one of the method used to preserve the fish to make it last longer than usual period of time. Traditionally, the most common method used is by drying the fish under the sun. However, this method is limited by unpredictable weather where sometimes the drying process is disturbed by the rain. In order to overcome the problem, this project is implemented by using a building protected from outside environment called drying house to enhance the drying process. A hardware system was introduced in this project which consists of monitoring and controlling part conducted by a microcontroller called Raspberry Pi. Monitoring part consists of temperature and humidity sensor, and light intensity sensor and connected to the microcontroller. These sensors are used to monitor the current condition inside the drying house for 24 hours daily. All the information gathered by the sensors was transmitted to the microcontroller to analyse. Then, the processed data were published via the Internet and displayed in Cayenne application through computer and smartphone application. The analysis for the condition inside the drying house was made based on the processed data. The results showed that the temperature and relative humidity is dependent each other and affected by the weather changes. The controlling part was introduced to keep maintain the temperature and relative humidity by generating heat using a gas heater and dehumidifier to reduce the air moisture. However, some problems were found during the experiment which affects the overall developed system.